2011
DOI: 10.1111/j.1525-139x.2011.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in Acute Kidney Injury: Lessons Learned and Applied

Abstract: Peritoneal dialysis (PD) is a simple, safe, gentle, and efficient renal replacement therapy (RRT) method. It is able to correct acute kidney injury (AKI)-induced metabolic, electrolytic, and acid-base disorders and volume overload both in and out the intensive care unit setting. Some PD modalities, such as high-volume PD and continuous flow PD, can provide RRT doses and efficiency comparable to extracorporeal blood purification methods. PD is particularly suitable for children, patients with refractory heart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 80 publications
1
38
1
1
Order By: Relevance
“…Our results are similar to the results of previous studies that showed that PD clearance was limited by dialysate flow, membrane permeability, and area (6)(7)(8)(9)(10)(11)(20)(21)(22)(23)(24)(25)(31)(32)(33)(34)(35). A 2-L exchange with a dwell time of 30 minutes can achieve dialysate saturation of around 50%.…”
Section: Discussionsupporting
confidence: 81%
“…Our results are similar to the results of previous studies that showed that PD clearance was limited by dialysate flow, membrane permeability, and area (6)(7)(8)(9)(10)(11)(20)(21)(22)(23)(24)(25)(31)(32)(33)(34)(35). A 2-L exchange with a dwell time of 30 minutes can achieve dialysate saturation of around 50%.…”
Section: Discussionsupporting
confidence: 81%
“…Guideline P2.3 -Automated PD Systems: Automated PD employing a cycler was introduced into clinical practice in the 1980s, decreasing the frequency of peritonitis and providing efficient metabolic and electrolyte control in AKI patients (88,89). Automated PD offers a wide selection of highly efficient treatment schedules obtained through the use of short dwell times, high dialysate flows, and customized intraperitoneal volumes (IPVs).…”
Section: Pediatric Guidelinesmentioning
confidence: 99%
“…TPD provides continuously to correct volume and metabolic disturbance without causing hemodynamic instability and it has better cardiovascular tolerance. [17][18][19] Therefore, TPD is a feasible option for the treatment of selected patients with ARF, especially newborns and infants, and those who are hemodynamically compromised and have severe coagulation abnormalities, difficulty in obtaining vascular access, and inborn metabolic disorder. Our reason to choose TPD in our patients was that most of them were newborns and infants who had acute kidney injury and/or inborn metabolic disorders and were hemodynamically unstable.…”
Section: Discussionmentioning
confidence: 99%